Performing Citizenship Bodies, Agencies, Limitations - Hildebrandt, Paula; Evert, Kerstin; Peters, Sibylle; Schaub, Mirjam; Wildner, Kathrin; Ziemer, Gesa (Performance Philosophy, 2019)
This open access book discusses how citizenship is performed today, mostly through the optic of the arts, in particular the performing arts, but also from the perspective of a wide range of academic disciplines such as urbanism and media studies, cultural education and postcolonial theory. It is a compendium that includes insights from artistic and activist experimentation. Each chapter investigates a different aspect of citizenship, such as identity and belonging, rights and responsibilities, bodies and materials, agencies and spaces, and limitations and interventions. It rewrites and rethinks the many-layered concept of citizenship by emphasising the performative tensions produced by various uses, occupations, interpretations and framings.